HBME-1 expression in differentiating benign and malignant thyroid lesions - Noor ‘Ain MN,; Nordashima Abd Shukor,; Mohd Rohaizat Hassan,; Mazne M,; Azyani Yahaya, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Thyroid carcinomas are classically diagnosed based on specific morphological criteria. In some cases, a definitive diagnosis may be difficult when morphological features are equivocal. This study evaluated the utility of Hector Battifora Mesothelial-1 (HBME-1) as an immunohistochemical marker to differentiate malignant from benign thyroid lesions and to compare its expression in different types of thyroid lesions. The sensitivity and specificity of HBME-1 as a specific marker for thyroid carcinoma were also studied. A total of 54 malignant and 54 benign thyroid cases diagnosed were collected in Universiti Kebangsaan Malaysia Medical Centre for a period of seven years. All cases were stained with HBME-1 and evaluated by three independent observers. The cases were scored based on the proportion of staining and graded as 0 (less than 10%), 1+ (10-25%), 2+ (26-50%) or 3+ (more than 50%). In addition, the score of malignant cases was correlated with their pathological tumour stage. HBME-1 showed significantly higher expression in malignant compared to benign lesions (P<0.001) with papillary thyroid carcinoma (PTC) showed the highest expression among the carcinoma cases (87.1%). Benign lesions were mostly negative (96%), except for two follicular adenoma cases having focal positivity. HBME-1 had a sensitivity of 57% and specificity of 96% in thyroid carcinoma. There was no correlation between HBME-1 expression and TNM primary tumour stage (pT). HBME-1 might be a useful marker in distinguishing malignant from benign thyroid lesions, especially in PTC cases.